Strengthening of ICT in the teaching-learning process for teachers (Revista Ciencia Agraria, 2022)
Introduction. Currently, the use of Information and Communication Technologies is of vital importance in any field, even more so in the field of education, since teachers must have resources and teaching tools that allow them to work on each of their subjects. in a creative way, so that the classes become dynamic and thus the teaching-learning process is attractive for each of the students, since they manage and know the technological environment, and for this reason, educators must be trained, trained and be interested in including the application of ICTs within their topics. Goal. Strengthen the use of ICT in teachers of the Ipiales Sectional Autonomous University Corporation of Nariño in virtual training to improve the construction of knowledge in the teaching-learning process. Materials and methods. Survey formats, field diaries, informed consent, diagnosis. Results. It was possible to show that it is necessary to strengthen the use of ICT, for this, some categories were determined that allowed the analysis to be carried out, such as lack of training, age, ignorance of ICT, lack of interest, among others.
Keywords: digital literacy; virtual learning environments; e-learning; learning management system; LMS; NTICs; TICs